1999
DOI: 10.1242/dev.126.19.4235
|View full text |Cite
|
Sign up to set email alerts
|

Shade avoidance responses are mediated by the ATHB-2 HD-Zip protein, a negative regulator of gene expression

Abstract: The ATHB-2 gene encoding an homeodomain-leucine zipper protein is rapidly and strongly induced by changes in the ratio of red to far-red light which naturally occur during the daytime under the canopy and induce in many plants the shade avoidance response. Here, we show that elevated ATHB-2 levels inhibit cotyledon expansion by restricting cell elongation in the cotyledon-length and -width direction. We also show that elevated ATHB-2 levels enhance longitudinal cell expansion in the hypocotyl. Interestingly, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 302 publications
(37 citation statements)
references
References 50 publications
1
30
0
Order By: Relevance
“…The AtHB2/HAT4 is strongly induced under the dark condition in the etiolated seedlings [100]. To confirm their function, transgenic lines overexpressing AtHB2/HAT4 produced longer hypocotyls [101]. This indicated that AtHB2/HAT4 is responsible for controlling the growth of seedlings in fluctuating light conditions.…”
Section: Light Stressmentioning
confidence: 97%
“…The AtHB2/HAT4 is strongly induced under the dark condition in the etiolated seedlings [100]. To confirm their function, transgenic lines overexpressing AtHB2/HAT4 produced longer hypocotyls [101]. This indicated that AtHB2/HAT4 is responsible for controlling the growth of seedlings in fluctuating light conditions.…”
Section: Light Stressmentioning
confidence: 97%
“…Some of the TFs we identified are closely related to members of the large HD‐ZIP class of transcriptional regulators; these were of particular interest to us here. Some members of this group have also been reported to be induced by shade and could promote the shade avoidance response (Carabelli et al., 2018; Sorin et al., 2009; Steindler et al., 1999). For example, ATHB1 , ATHB16 (both HD‐ZIP class I), ATHB2 , and ATHB4 (both HD‐ZIP class II) were reported to have a role in light responses (Aoyama et al., 1995; Carabelli et al., 1993, 1996; Sorin et al., 2009; Steindler et al., 1999; Wang et al., 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Some members of this group have also been reported to be induced by shade and could promote the shade avoidance response (Carabelli et al., 2018; Sorin et al., 2009; Steindler et al., 1999). For example, ATHB1 , ATHB16 (both HD‐ZIP class I), ATHB2 , and ATHB4 (both HD‐ZIP class II) were reported to have a role in light responses (Aoyama et al., 1995; Carabelli et al., 1993, 1996; Sorin et al., 2009; Steindler et al., 1999; Wang et al., 2003). Two other class I HD‐ZIP TFs and one class II HD‐ZIP TF were in the core set of shade‐upregulated TFs identified in this study (Figure S9), namely VfHB7.1 , VfHB7.2 , and VfHAT22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, 25 are TFs and 15 of these appeared as main regulators of the inferred regulons (Supplemental Table 2). Examples include genes known to be involved in root morphogenesis such as KNAT7 and HAT4 (Steindler et al, 1999;Zhong et al, 2008), but more interestingly, also genes with unknown functions such as AT2G03470 in xylem-31, WRKY3 in trichoblast-27, and bZIP6 in several stele-related clusters.…”
Section: Identification Of Known and Novel Root-related Tfs Among The...mentioning
confidence: 99%